Strengthening students' character through TPACK-based learning - Chotimah, Umi; Yanzi, Hermi; Kurnisar, Kurnisar; Faisal, Emil El; Yusuf, Muhammed; Susanti, Emi (Universitas Negeri Yogyakarta, 2022)
This study aims to describe strengthening students' character through TPACK-based learning. It's implemented in Pancasila and Civics Education teaching and learning process at SMA Negeri 1 Palembang, one of favorite high school in Palembang city. Although this school has been recognized as a superior school and is the oldest public high school in the city of Palembang, but this school is still focused on students' character. The data collection used in this study were observation, questionnaire, and documentation. It's implemented by applying TPACK-based learning with teaching materials which was held four times. Data were analyzed by comparing the results of observations before and after learning. Based on the result and discussion, it can be concluded that strengthening students' character can be improved through the application of TPACK-based learning. The TPACK-based learning includes the teacher's ability to design and applied technology (a learning video developed, power point media, values cases), pedagogy (models of teaching, teaching approaches, teaching strategy and methods), and content knowledge that integrates characters, namely religious values, nationalism, independence, integrity, and cooperation the course values relevant to the learning objectives and indicators of basic competencies so that it makes teaching and learning process can strength the students' character and very interactive, joyful and achieve learning objectives.